The "Subject" and Black Queer Religious Discourse: A Review of and Response to Representations of Homosexuality By Roger A. Sneed - Aymer, Margaret P. (Black theology : an international journal, 2012)
This article is a brief response to Roger A. Sneed's groundbreaking book Representations of Homosexuality. This critique is written by a New Testament scholar who nonetheless seeks to engage with the critical theologizing of the author from that vantage point. This response was delivered at a Black Theology panel dedicated to Sneed's book at the 2011 meeting of the American Academy of Religion, in San Francisco.